Modelling the interaction between vegetation and infiltrated stormwater - Poozan, Abolfazl; William Western, Andrew; James Burns, Matthew; Arora, Meenakshi (Journal of hydrology (Amsterdam), 2022)
•Interaction between vegetation and infiltrated stormwater is simulated for a system.•Evapotranspiration decreases 13% in absence of infiltrated stormwater.•Infiltration basins should be placed near waterways to increase baseflows. A major problem associated with sealing native soils with impervious surfaces in urban areas is reduced groundwater recharge. This in turn reduces stream baseflows which has serious implications for freshwater ecosystems. To address this problem, the use of stormwater infiltration systems is becoming increasingly common worldwide. There is, however, substantial uncertainty on the fate of infiltrated stormwater and its interactions with downslope vegetation. This study aimed to investigate the role of vegetation on the amount of infiltrated stormwater reaching the stream. A model using MIKE SHE was constructed, calibrated, and validated based on a real infiltration system which features extensive vegetation between the site of stormwater infiltration and the stream. We then used the calibrated model to predict the amount of infiltrated stormwater reaching the stream in the absence of vegetation. We also predicted the impact of infiltrated stormwater on the evapotranspiration downslope of the system. The results showed that the performance of the model was satisfactory, and the model captured the overall groundwater dynamic very well. The amount of infiltrated stormwater reaching the stream increased by about 17 percent in the absence of vegetation. The model also predicted that evapotranspiration would be 13 percent lower in the warmer months if stormwater was not infiltrated upslope. The results suggest that the choice of location of infiltration systems should consider the potential of vegetation to intercept infiltrated water and impact on achievement of the design objectives, which, in this case, included restoring baseflow. Where increasing the baseflows is not a priority, the increased evapotranspiration afforded by stormwater infiltration could provide important microclimate benefits.